TEORI PERMINTAAN DALAM PERSPEKTIF EKONOMI ISLAM DAN KONVENSIONAL - Nine Haryanti (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2019)
ABSTRACTMicroeconomic theory is one of the branches of science that is very important insociety, where people to meet their needs will create demand. Studying from an Islamicand conventional perspective on demand, in general, is almost the same. This studyaims to find out how the theory of demand in Islamic and conventional viewpoints.Using a descriptive qualitative method, collecting data by combining from severalsources and discussions with students of Islamic economics majoring in SiliwangiUniversity. So, from the results of research on legal sources that are used by Islamicboundaries in view of demand, from the existence of different views about commoditiesand objectives to be achieved. The main source of the theory of Islamic demand is theQur'an, al-hadith, and as-sunnah of the Prophet Muhammad. Meanwhile, inconventional theory, human reason is sometimes not even rational when buying anumber of commodities for goods or services.